1995
DOI: 10.1007/bf00017680
|View full text |Cite
|
Sign up to set email alerts
|

Response of ?criollo? maize to single and mixed species inocula of arbuscular mycorrhizal fungi

Abstract: We tested the effect of two single species inocula and a mixed inoculum of the native population of arbuscular mycorrhizal (AM) fungi on the growth response of "criollo" maize (Zea mays L.). To determine the inocula that produced the highest response on maize growth, we conducted a greenhouse experiment at 3 levels of P fertilization (0, 40 and 80 kg ha-l). Inoculation with Glomus mosseae (Nicolson and Gerdemann) Gerd. and Trappe (LMSS) produced the greatest shoot growth rates at the two lowest P fertilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 22 publications
1
12
0
2
Order By: Relevance
“…Some research has suggested that inoculation with a mixed community of AMF species could potentially be more beneficial than use of a single isolate (Jansa et al 2008;Maherali and Klironomos 2007), whereas other research suggest no additive effect (Daft 1983;Gavito and Varela 1995;Janoušková et al 2009). No previous work has tested the effect of a mixed inoculum in a range of plant genotypes.…”
Section: Discussionmentioning
confidence: 94%
“…Some research has suggested that inoculation with a mixed community of AMF species could potentially be more beneficial than use of a single isolate (Jansa et al 2008;Maherali and Klironomos 2007), whereas other research suggest no additive effect (Daft 1983;Gavito and Varela 1995;Janoušková et al 2009). No previous work has tested the effect of a mixed inoculum in a range of plant genotypes.…”
Section: Discussionmentioning
confidence: 94%
“…Gavito & Varela (1995), por exemplo, pretenderam cultivar e testar 14 espécies de uma comunidade fúngica associada com milho, mas eles obtiveram sucesso com apenas duas espécies. Neste estudo, apenas de três a cinco espécies foram isoladas das comunidades, mas é provável que outros fungos menos agressivos e que não estavam esporulando possam estar presentes na comunidade original, visto que três a cinco espécies de FMAs podem ser consideradas uma comunidade micorrízica relativamente simples (Morton et al, 1995).…”
Section: Discussionunclassified
“…In maize, the benefit to the plant can vary depending on the fungal species, soil P status, and genotype (Gavito and Varela, 1995;Kaeppler et al, 2000;Bressan and Vasconcellos, 2002;Wright et al, 2005;Sawers et al, 2010). Studies realized with maize inbred lines indicate that mycorrhizal responsiveness of maize genotypes under low P, rather than the interaction with the mycorrhizal fungus as such, is a key factor in determining benefit (Kaeppler et al, 2000), although further analyses have suggested that maize germplasm may indeed harbor significant variation in the ability to profit from mycorrhizal interaction per se (Sawers et al, 2010).…”
Section: Association With Mycorrhizamentioning
confidence: 99%